IMPLEMENTASI POLITIK HUKUM PIDANA DALAM MELINDUNGI KORBAN KEJAHATAN - Sagita, Andi; Wahyuni, Fitri (JURNAL RISET INDRAGIRI, 2024)
Protection of crime victims is part of the protection of human rights as a whole. The politics of criminal law regarding the protection of crime victims is regulated in the Criminal Procedure Code and Law No. 13 of 2006. This writing aims to find out how the politics of Indonesian criminal law are applied and to find out how the politics of Indonesian law provides protection for crime victims. This research method uses normative juridical legal research. The result of this writing is that the application of Indonesian legal politics is formulated in the Criminal Code, Criminal Procedure Code, and Regulations that regulate criminal provisions, Indonesian criminal law policies in protecting crime victims have not been specifically regulated and adequate regulations were issued, Law Number 13 of 2006 was only intended to protect witnesses. in cases of criminal acts of corruption. Keywords: criminal law politics, protection of crime victims, evidence